الأمن الإنساني والتنمية المستدامة في المنطقة المغاربية:دراسة في الواقع والتحديات - خلف الله عمر (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
يعد النقاش حول موضوع الأمن الإنساني والتنمية المستدامة امتدادا لتطور نظري عرفه مفهومي الأمن والتنمية، وفي هذا السياق قدمت مقاربة الأمن الإنساني كمقاربة جديدة تتسم بالشمولية وتجعل من الفرد محورا للأمن. وبالموازاة جاء مفهوم التنمية المستدامة للدفاع عن فلسفة الحفاظ على الثروة والموارد لضمان مبدأ تكافؤ الفرص بين الأجيال. إنّ دراسة المنطقة المغاربية وفقا للمدخلين السابقين تكشف حالة من العجز عكسها الواقع الذي يعيشه الفرد في دول المغرب العربي، وهو ما يطرح مجموعة من الأسئلة لعل أبرزها كيف يمكن تشخيص واقع الأمن الإنساني والتنمية المستدامة في المنطقة المغاربية، وكنتيجة أولية لهذا النقاش يمكن القول أنّ الفشل في بناء الدولة الحديثة يعد سببا جوهريا يعقد تحديات الأمن الإنساني والتنمية المستدامة في الدول المغاربية. The debate on the human security and the sustainable development is the theoretical evolution of the concepts of security and development. In this context, the human security approach has been introduced as a new comprehensive approach that focuses on the individuals as the core of security. On the other hand, the concept of sustainable development defends the idea of not compromising the wealth and resources of future generations. Studying the Maghreb region in the light of the two previous concepts shows a sort of inability reflected by the hard reality of individuals in the said region. This situation raises many questions; the most important is how to go through the reality of the human security and the sustainable development in the Maghreb region. As a preliminary finding to this debate, we can say that the main cause of the complexity of the challenges of the sustainable development and the human security in this region is the failure in the construction of modern states.